Research on the Impact of Internal Control on Small Business Management: A Case Study In Peru – 2023 - Gonzales Renteria, Yuri Gagarin; Aniceto Gonzales, Lourdes Marina (Journal of Ecohumanism, 2025)
Internal control and administrative management are powerful and fundamental tools in a company’s organization, as they work together to safeguard and protect assets, minimize errors, and ensure proper operation. This research aimed to determine the impact of internal control on the administrative management of small businesses in Latin America and of Dinogas Estaciones y Servicios SAC - Chimbote, 2023. The methodology used was qualitative, descriptive, and non-experimental. Data collection techniques such as bibliographical exploration and interviews, as well as bibliographical cards and a questionnaire, were used to gather information. The results showed that: internal control is a process that as it is executed improves the administrative management in the company, achieving the proposed objectives, however, the investigated company does not have an internal control system in place, which is why it presents multiple weaknesses and threats such as loss of financial and administrative documentation, duplication of functions, financial statements with unreliable information, product inventories with unreal balances, therefore it is mandatory to implement an internal control system so that the administrative management can develop its controls effectively and efficiently, likewise it was concluded that internal control favorably influences and strengthens the administrative management by reducing costs and expenses that will benefit the company to achieve the objectives set and make correct decisions.